LIGHT-RAILS MODEL IN TEMPE, ARIZONA: STRATEGIES TO REDUCE AIR POLLUTION - Hammarstrom Dobler, Guilherme; La Bianca, Alexander; Tissot Squalli Houssaini, Mara Lisiane (Revista Contexto & Saúde, 2017)
To rethink growth is important to keep up with an increase demand of transport in order to decrease greenhouse gas emissions. It is clear that transportation generates a loss in vegetation then leads to an increase of carbon dioxide, a prime contributor to global warming, in the atmosphere. However, new alternatives are available to show an attempt to solve congestion that ultimately promotes a further increase of pollutants in the atmosphere. From this insight, we find solutions to resolve traffic problem in the megalopolis Phoenix, in particular the city of Tempe. Although this research we highlight the factors that make up a good ridership of the Phoenix light rail looking at similar low density cities like Phoenix, we searched for solutions that would prevent low ridership in future light rail extensions. It was found that a more pedestrian friendly environment was created with businesses and residential buildings close together, especially in Tempe City around the Arizona State University (ASU), extremely benefited by the project.